Representativeness of the mammalian collection of the Zoological Museum of Lviv University - Zatushevskyy, A.; Shydlovskyy, I.; Tymkiv, I. (Праці теріологічної школи, 2016)
During collection inventorization of the Zoological museum of Lviv University we found that there are nearly 3800 exhibits belonging to 258 mammal species of the world’s fauna. Most of the samples (68 %) represent the order of rodents (Rodentia). In systematic aspect, mammalian collections consist of representatives of 20 orders. The collections were founded by 264 persons, 28 of them made the main contribution. It is necessary to mention species listed in the Red Date Book of Ukraine: one species belongs to the category Extinct in the Wild (European bison), two — Extinct (Schreibers’s long-fingered bat, European ground squirrel), three — Data Deficient (bicolored shrew, lesser blind mole rat, gray dwarf hamster), five — to the category Not Evaluated (Nathusius’ pipistrelle, European otter, short-tailed weasel, European polecat, common hamster). In addition, 9 species are rare, 12 belong to the category Endangered, and 18 are vulnerable in our country. Among representatives of mammals, in the museum’s collections there are 229 species included into the Red List of the International Union for Conservation of Nature (Version 2015-4) belonging to six conservation status categories. The rarest ones among them are the species, which belong to the Critically Endangered category, such as the black-and-white ruffed lemur, diademed sifaka, Sunda pangolin, European mink, black rhinoceros, long-tailed chinchilla. Інвентаризацією колекцій Зоологічного музею Львівського Університету встановлено, що у фондах зберігаються понад 3 800 зразків 258 видів ссавців фауни світу. Більша частина зразків, а саме, 68 % — це представники ряду Гризуни (Rodentia). У систематичному плані, колекції ссавців складають представники 20 рядів. Фундаторами стали 264 особи, з яких 28 зробили основний внесок. Варто відзначити види, що занесені до Червоної книги України: один — зниклий у природі (зубр), два — зниклі (довгокрил звичайний, ховрах європейський) ці види мають такий статус згідно Червоної книги України: три — недостатньо відомі (білозубка велика, сліпак білозубий, хом’ячок сірий), п’ять — неоцінені (нетопир лісовий, видра звичайна, горностай, тхір лісовий, хом’як звичайний), 9 — рідкісні, 12 — зникаючі та 18 — вразливі. Представники теріофауни, занесені до Червоної книги МСОП, охоплюють шість категорій охоронного статусу 229 видів. Найрідкіснішими серед них є ті, які належать до критично загрожених, зокрема: лемур варі, сифака діодемовий, панголін яванський, норка європейська, носоріг чорний, шиншила.